Impact of involving the community in entomological surveillance of Triatoma infestans (Klug, 1834) (Hemiptera, Triatominae) vectorial control - Abrahan, Luciana Beatriz (2021)
Background: Vectorial transmission is the principal path of infection by Trypanosoma cruzi, the parasite that causes Chagas disease. In Argentina, Triatoma infestans is the principal vector; therefore, vector control is the main strategy for the prevention of this illness. The Provincial Program of Chagas La Rioja (PPCHLR) carries out entomological evaluation of domiciliary units (DUs) and spraying of those where T. infestans is found. The lack of government funds has led to low visitation frequency by the PPCHLR, especially in areas with a low infestation rate, which are not prioritized. Therefore, seeking possible alternatives to complement control activities is necessary. Involving householders in entomological evaluation could be a control alternative. The major objective was to determine the cost of entomological evaluation with and without community participation. Methods: For entomological evaluation without community participation, PPCHLR data collected in February 2017 over 359 DUs of the Castro Barros Department (CBD) were used. For entomological evaluation with community participation, 434 DUs of the same department were selected in November 2017. Each householder was trained in collecting insects, which were kept in labeled plastic bags, recovered after 2 weeks, and analyzed in the laboratory for the presence of T. cruzi. Using householders' collection data, a spatial scan statistic was used to detect clusters of different T. infestans infestations. Entomological evaluation costs with and without community participation related to the numbers of DUs visited, DUs evaluated, and DUs sprayed were calculated and compared between methodologies. In addition, the number of DUs evaluated of the DUs visited was compared. Results: According to the results, the triatomines did not show evidence of T. cruzi infection. Spatial analysis detected heterogeneity of T. infestans infestation in the area. Costs related to the DUs visited, evaluated, and sprayed were lower with community participation (p < 0.05). In addition, more DUs were evaluated in relation to those visited and a greater surface area was covered with community participation. Conclusion: Participation of the community in the infestation survey is an efficient complement to vertical control, allowing the spraying to be focused on infested houses and thus reducing the PPCHLR's costs and intervention times.[Figure not available: see fulltext.]